Application of SDN deployment in large-scale public cloud across different resource pools - Qiu YUE; Qin LIU; Xiaole YANG; Xiaofei BI; Shixuan ZHU (Dianxin kexue)
The SDN-based network solution for cloud computing data center is the trend of future data center network development.For the current mobile operator network,the outstanding application case where SDN network technology has been applied and successfully launched was discussed.The case was also one of the largest SDN commercial cases among global operators.The key issues and introduction steps for the large-scale deployment of SDN in cloud data centers were summarized based on the current network operating conditions,which could provide the reference for SDN architectures deployment in other cloud computing resource pools such as the NFV and 5G network.